The political economy of the 2014 farm bill - Orden, David; Zulauf, Carl (Agricultural and Applied Economics Association, 2015)
This article assesses the political economy of the 2014 farm bill, which eliminated annual fixed direct payments but offers enhanced downside risk protection against low prices or declining revenue. The farm bill secured substantial bipartisan majorities in a politically contentious Congress. The countercyclical structure of U.S. support is reaffirmed and crop insurance is enhanced as a safety net pillar. Open policy issues include the distribution of benefits among crops, the design of multiple year support around moving-average revenue benchmarks versus fixed references prices, and questions related to crop insurance, including the overall level of premium subsidies. In an international context, we conclude the 2014 farm safety net likely would not have been enacted had multilateral agreement been reached on the 2008 Doha Round negotiating documents; conversely, the 2014 farm bill makes achieving those limits more difficult. Orden, David; Zulauf, Carl R.